EVALUATION OF DRUG INFORMATION SERVICES IN PATIENTS WITH DIABETES MELLITUS IN OUTPATIENT INSTALLATIONS GENERAL HOSPITAL PHARMACY COAL REGION - S, Aminah .; M. Br Turnip, Nur Ulina; ., Mahliza (Jurnal FARMASIMED (JFM), 2023)
Based on people's unhealthy lifestyle habits and from data on the five biggest diseases for the period July – September 2022 which shows that diabetes mellitus occupies the second level of the five biggest diseases in Batu Bara Hospital, and drug information services are very necessary because there are many patients who still do not understand what to do about drugs, this is done to minimize abuse and interactions between drugs that are not wanted by patients. To find out how drug information services are for DM patients at the Batu Bara Hospital pharmacy installation on an outpatient basis, and to identify the completeness of the information provided by pharmaceutical staff to patients at the Framing Installation at the Batu Bara General Hospital, and also to find out the problems found in technical drug information services provided to patients at the Batu Bara Regional Hospital Pharmacy Installation. This type of research is an observational study. The design of this study is qualitative by making direct observations or observations, interviews and documentation. Drug information services for diabetes mellitus patients in outpatient care at the Batu Bara Hospital pharmacy installation were in the very good category with a result of 96%. Drug information services performed by eight pharmacists consisting of six pharmacists and two pharmacy technicians for outpatient diabetes mellitus patients at the Batu Bara Hospital pharmaceutical installation have met the standards in the very good category with a yield of 96%.